Sosialisasi Model Pembelajaran Problem Based Learning dengan Metode Team Games Tournament Kepada Guru Kelas SD Negeri 19 Ampenan - Azizah, Baiq Hidayatul; Ramdhani, Fitra Rizki; Hidayah, Khulaeni Hidayatul; Tabroni, Muhammad; Al Qorni, Wais (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
The increasing age of education, especially in Indonesia, does not rule out the possibility of poor learning outcomes. Learning outcomes are one of the important aspects during the learning process. With a learning outcome we can see whether the learner's goals have been achieved or not. To achieve a result, in the teaching and learning process it is recommended to choose an appropriate learning method so that it can be implemented in the class or material that will be taught. To achieve this goal, one method that is suitable and can be used is the problem based learning (PBL) learning model with teams games tournament (TGT). The implementation method used is the first stage is socialization, the second stage is implementing the PBL model with TGT and the third stage is carrying out discussions with the class teacher. The results of the implementation of the PBL model with TGT are that the individual scores and average scores of students are getting better so that the use of the PBL learning model with TGT has an effect on improving student learning outcomes. Abstrak Semakin meningkatnya usia pendidikan khususnya di Indonesia tidak menutup kemungkinan adanya hasil belajar yang kurang baik. Hasil belajar ialah salah satu aspek yang penting selama proses belajar. Dengan adanya suatu hasil belajar kita dapat melihat apakah tujuan pembelajar sudah tercapai atau belum. Tercapainya suatu hasil, dalam proses belajar mengajar disarankan memilih metode pembelajaran yang sesuai agar dapat diimplementasikan dalam kelas atau meteri yang akan diajarkan. Untuk mencapai tujuan pembelajaran tersebut, salah satu metode yang sesuai dan dapat digunakan adalah model pembelajaran problem based learning (PBL) dengan teams games tournament (TGT). Metode pelaksanaan yang digunakan yakni tahap pertama ialah soisalisasi mengenai model pembelajaran yang akan digunakan, tahap kedua ialah implementasi model PBL dengan TGT dan tahap ketiga ialah melaksanakan diskusi dengan guru kelas. Hasil pelaksanaan dari digunkannya model PBL dengan TGT ini ialah nilai inividu dan nilai rata-rata peserta didik menjadi semakin baik sehingga penggunaan model pembelajaran PBL dengan TGT berpengaruh terhadap meningkatnya hasil belajar peserta didik.